A Systematic Review of Spironolactone Nano-Formulations for Topical Treatment of Skin Hyperandrogenic Disorders and Chronic Wounds - Saedah Dereiah; Muhammad Usman Ghori; Barbara R. Conway (Pharmaceutics)
Background/Objectives: Spironolactone (SP), an aldosterone inhibitor widely used to treat androgen-dependent disorders such as acne, hirsutism, and alopecia, has demonstrated therapeutic potential in both oral and topical formulations. However, SP’s low solubility and poor bioavailability in conventional formulations have driven the development of novel nanocarriers to enhance its efficacy. This review systematically examines recent advancements in SP-loaded nanocarriers, including lipid nanoparticles (LNPs), vesicular nanoparticles (VNPs), polymeric nanoparticles (PNPs), and nanofibers (NFs). Methods: A search strategy was developed, and the relevant literature was systematically searched using databases such as Scopus, PubMed, and Google Scholar. The review process, including screening, inclusion, and exclusion criteria, adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: A comprehensive analysis of 13 eligible research articles, corresponding to 15 studies, highlights key aspects such as encapsulation efficiency, stability, particle size, and in vitro and in vivo efficacy. Six studies focused on lipid nanoparticles (LNPs), including solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs), which were found to improve SP’s bioavailability and skin permeation. Another six studies investigated vesicular nanoparticles (VNPs), such as ethosomes and niosomes, demonstrating superior skin targeting and penetration capabilities. Two studies on polymeric nanoparticles (PNPs) showed effectiveness in delivering SP to hair follicles for the treatment of alopecia and acne. Additionally, one study on SP-loaded nanofibers indicated significant potential for topical rosacea therapy. Conclusions: SP-loaded nanocarrier systems represent promising advancements in targeted topical therapy. However, further clinical studies are required to optimize their safety, efficacy, and delivery mechanisms.